(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims at studying the chronological order that resulted from the word change in the Arabic sentence and its effect on the meaning that is the focus, before adding it to the literary text. The research is an analytical study of the poem “Hahona Alaan “ that depicts what the poet Mahmoud Darwish wants to convey through the used chronological order that is used as a reference for various styles. The research also reveals the psychological status and the suppressed desire of the poet through the chronological order, and the effects of the past, the present, and the future in the emotional atmosphere of the whole poem .